(untitled) (REGE Revista de Gestão, 2024)
Purpose – The study investigated the effect of marketing communications’ dimensions on brand loyalty in the banking sector. Design/methodology/approach - The study adopted the quantitative research approach which relied on the explanatory design due to the nature of the hypotheses tested. The convenience sampling technique was used to pull 377 customers of a branch of a commercial bank in Ghana. Furthermore, the PLS-SEM technique was deployed to assess the measurement model and test the research hypotheses. Findings - Results show that the following dimensions of marketing communications are significant predictors of brand loyalty: direct marketing, public relations, and sales promotion. The exception is advertising, which had an inverse relation with brand loyalty. Practical implications – The results provide significant pointers to banks’ management that they should deploy a variety of marketing communication channels other than intensive advertising to reach and persuade customers. Originality/value –The study illustrates the latest effort to extensively provide insights into how commercial banks could leverage marketing communication tools to sustain loyalty in an emerging economy that is intensively competitive.